2010
DOI: 10.1111/j.1365-2753.2010.01421.x
|View full text |Cite
|
Sign up to set email alerts
|

Interhospital variation in appropriateness of cataract surgery

Abstract: The variation in appropriateness of phacoemulsification cannot be attributed solely to the clinical differences between the hospitals' patients. There is room for improvement in the appropriate indication of phacoemulsification. Measures based on the dissemination of appropriateness criteria might improve quality of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…This study also showed that an improvement in BCVA did not correlate with an improvement in Catquest-9SF. This is counterintuitive to how other cataract surgery appropriateness instruments are designed to categorize patients [25]. Fig 4 shows no pattern in BCVA change for those patients who reported good Catquest-SF scores preoperatively and postoperatively.…”
Section: Discussionmentioning
confidence: 90%
“…This study also showed that an improvement in BCVA did not correlate with an improvement in Catquest-9SF. This is counterintuitive to how other cataract surgery appropriateness instruments are designed to categorize patients [25]. Fig 4 shows no pattern in BCVA change for those patients who reported good Catquest-SF scores preoperatively and postoperatively.…”
Section: Discussionmentioning
confidence: 90%
“…64,103,[126][127][128][129][130][131] The most common assumption for inappropriate surgery is a patient with VA above 20/40 (0.5) in both eyes. 64,103,[126][127][128][129][130][131] The most common assumption for inappropriate surgery is a patient with VA above 20/40 (0.5) in both eyes.…”
Section: Variability and Health Services Qualitymentioning
confidence: 99%